Saxon or European? Interpreting and Reinterpreting St Boniface - Palmer, James (History compass, 2006)
St Boniface (c.680-754) has been called one of the ‘founders of Christian Europe’ for his wide-ranging influence on religion, politics and culture in the early Middle Ages. This Anglo-Saxon was a missionary in Frisia, reformer in Germany, promoted papal authority, and supported the Carolingian seizure of royal power in Frankia in 751. Yet the precise significance of his achievements has always been subject to interpretation, invention and challenge. This essay explores some of the medieval and modern attitudes to Boniface, examining how and why representations of the saint remain varied and open to change. In particular it asks why the commemoration of St Boniface was divorced from the conversion of Saxony - a task he as an Anglo-Saxon had actively promoted - and instead became a matter of European meaning.